Sensitivity study of the Nordic and Barents Seas Atlantis model - Hansen, Cecilie; Drinkwater, Kenneth F.; Jähkel, Anne; Fulton, Elizabeth A.; Gorton, Rebecca; Skern-mauritzen, Mette (Seanoe, 2018)
The dataset was created for exploring the sensitivity of nine key species to four key parameters within the Atlantis framework of the Nordic and Barents Sea. Each simulation is 55 years long, including a 24 year spin-up time, and are all run without fisheries and climatic forcing, to exclude any variance coming from other sources than the parameter perturbations. The dataset includes one control run, and 104 parameter perturbations runs. Key species includes minke whales, northeast arctic cod, Norwegian spring spawning herring, polar cod, capelin, large, medium and small zooplankton and jellyfish. For each of these groups, key life history parameters such as growth rate, consumption rate, mortality rate and recruitment is changed, either as a one-at-a-time perturbation or as a combination of several parameters. The dataset includes biomass information for each of the 52 components of the model, such that both component response and system-level impact can be traced through all parameter perturbations.